People Who Leave No Trace: Dora Bruder and the French Immigrant Community - Mary Jean Green (Studies in 20th & 21st Century Literature, 2007)
Although the neighborhoods where Dora Bruder once lived are now crowded with more recent immigrants, Modiano seems to have erased the contemporary French immigrant community from his narration. Yet immigrants and their children, like Modiano's own father, are very much at the center of this text. In fact, the story of the bureaucratic subjugation of the Bruder family suggests parallels with issues affecting immigration in the book's narrative present in 1996 and 1997, especially the deportation proceedings instituted against immigrant children who, like Dora Bruder, were born in France. Despite their remarkable absence from the streets of Modiano's Paris, French immigrants of the narrative present become in his text visible through the traces of their absence, their history of colonial and post-colonial oppression offering ghostly echoes of long-repressed histories of war and Occupation.
Keywords: Dora Bruder; immigrant; Patrick Modiano; French immigrant; French immigrant community; deportation; colonial oppression; post-colonial oppression; oppression